Histopathology Studies of Selected Organs of Hemichromis Fasciatus [1] Inhabiting Igun Gold Mining and Opa Reservoirs, South Western Nigeria: A Comparative Study - Emmanuel, Obayemi Oluwadamilare; Olusola, Komolafe Olaniyi (International Journal of Advances in Life Science and Technology, 2020)
This study examined histopathological alterations in the gills, fillet and liver of Hemichromis fasciatus in Igun reservoir (located in an abandoned goldmine area) compared to those of Opa reservoir. Fresh adult fish samples were collected from Opa and Igun reservoirs and identified in the laboratory. Techniques based on histological analyses were done on the organs and photomicrographs taken using digital binocular compound LED microscope. Epithelial lifting and hypertrophy of lamellae were observed in the gills of H. fasciatus in Opa reservoir compared to rupture of gill epithelium, rupture of chloride cell, fusion, hyperplasia, curling of lamellae in H. fasciatus of Igun reservoir. The fillet of H. fasciatus in Opa and Igun reservoirs revealed splitting and atrophy of muscle bundles. Also, parasite cyst and necrosis was observed in the fillet of H. fasciatus of Igun reservoir compared to degeneration in muscle bundles in the fish of Opa reservoir. Similarly, the liver of H. fasciatus in Igun and Opa reservoirs showed splitting at the wall of central vein, hepatopancreas and liver cells degeneration. Moreover, nucleus hypertrophy were also identified in the liver of H. fasciatus in Opa reservoir compared to vascular congestion in the central vein, bile duct, portal vein and portal artery of H. fasciatus in Igun reservoir. The study therefore concluded that H. fasciatus specimens in Igun reservoir are histopathologically unhealthy compared to those of Opa reservoir.